Evaluation of treatment of intra-bony defects with a mixture of ?-tricalcium phosphate - hydroxyapatite granules and oily calcium hydroxide suspension - Raed A Badiea (College of Dentistry/ University of Baghdad, 2014)
Background: An oily calcium hydroxide formulation proved over the last years to be highly efficient in promoting bone regeneration in closed defects as periapical lesions, cysts, or post-extraction defects. The aim of the present study is the assessment of the outcome of treatment of deep intrabony periodontal defects with an Open Flap Debridement) (OFD) + combination of {(30% Hydroxyapatite HAp + 70% ?-Tricalcium Phosphate granules mixed with an Oily Calcium Hydroxide Suspension (OCHS )} and compare the results with {(OFD) alone)}. The combination of OCHS& TCP was used in humans with a sort of positive results, and more conduction of studies was recommended. Material and method: The sample of this study composed of sixteen patients; each had at least two intrabony defect teeth. For each patient, one tooth was treated by OFD only (control group 16 teeth) and the other teeth (study group 16 teeth) were treated with OFD + a mixture of (OSTEON II- Korea) granules comprise of (30% Hydroxyapatite HAp + 70% ?-Tricalcium Phosphate) and OCHS (Osteoinductal, Osteoinductal GmbH., Muenchen, Germany). The clinical parameters that were measured and recorded included (Plaque index PLI, Gingival index (GI), Gingival recession(GR) , Bleeding on probing (BOP), probing pocket depth (PPD), clinical attachment level (CAL) and radiographical width & depth of the bony defect. These parameters were recorded before treatment (base line) & six months after the treatment. Results: The results after treatment revealed a highly significant reduction in all of the parameters except the PLI in both study & control groups compared to baseline (p < 0.001). The clinical results were indicated that the study group showed significant reductions of PPD and CAL mean values more than improvements obtained by the control group with significant difference (p < 0.05). Conclusions: An excellent postoperative improvement in clinical parameters was noticed in the study group more than control group and the differences were significant. Thus the present study has revealed that the treatment modality of OFD + a combination of granules comprise of (30% Hydroxyapatite HAp + 70% ?-Tricalcium Phosphate) mixed with oily Calcium Hydroxide suspension is successful, predictable and more beneficial than (open flap debridement) (OFD) alone in the treatment of deep intrabony periodontal defects.